Nieunikniona przełomowość wędrowania. Stawanie się przybyszem według Hermanna Hessego - Dobek, Mieszko (Przestrzenie Teorii, 2025)
The article is dedicated the work of Hermann Hesse, with a particular focus on the representations of the newcomer figure within them. By analyzing two of his novels – Peter Camenzind (1904) and Siddhartha (1922) – the author seeks to define the specificity of this figure and the narrative-philosophical similarities between the two works. A particularly important issue is the broadly understood problem of wandering and how it is implemented by individual characters in the novel. The author also juxtaposes the German prose writer’s viewpoint with the thought of European philosophers, such as Emmanuel Lévinas or Bernhard Waldenfels, as their inquiries also focus on the problem of meeting the other and the possible interactions that an individual can adopt to make the titular stranger part of a given community without giving up their own identity.